Structural insight into the substrate-binding mode and catalytic mechanism for MlrC enzyme of Sphingomonas sp. ACM-3962 in linearized microcystin biodegradation - Guo, Xiaoliang; Li, Zengru; Jiang, Qinqin; Cheng, Cai; Feng, Yu; He, Yanlin; Zuo, Lingzi; Rao, Li; Ding, Wei; Feng, Lingling (Frontiers in Microbiology, 2023)
So far, microcystins (MCs) have caused extremely hazardous to ecological environment and public health. How to remove MCs safely and effectively has became an urgent global problem. The high-efficiency removal of MCs can not be achieved only relying on natural degradation. Therefore, microcystinases derived from indigenous microorganisms have received widespread attention due to their specific MCs biodegradation function. As the first intermediate products of MCs, linearized MCs are also very toxic and need to be removed. As the key hydrolase that can specifically degrade linearized MCs into almost non-toxic product Adda, MlrC is essential for the complete detoxification of MCs. However, how MlrC binds to linearized MCs and how it catalyzes the degradation process based on the real three-dimensional structure have not been determined yet. In this study, according to combination with molecular docking and site-directed mutagenesis methods, the binding mode of MlrC and linearized MCs was explored. A serial of substrate binding key sites including E70, W59, F67, F96 and others were pointed out. The active center of MlrC was made up of catalytic center and substrate binding center, and the relationship between MlrC enzyme, zinc ion and substrates was analyzed in detail for the first time. Finally, based on experimental results and literature survey, the possible catalytic mechanism of MlrC enzyme was further proposed. These findings provided new insights into the molecular mechanisms of MlrC enzyme to degrade linearized MCs, and laid a theoretical foundation for the further biodegradation study of MCs.